Plasmodium vivax treatments: what are we looking for? - Price, R; Douglas, N; Anstey, N; von Seidlein, L (2011)
PURPOSE OF REVIEW: For over 50 years, the treatment of Plasmodium vivax has relied on a combination of chloroquine and primaquine, but this strategy is under threat. Chloroquine efficacy is now compromised across much of the vivax endemic world and there are significant operational difficulties in deploying primaquine. We review the recent advances in P. vivax chemotherapy that may influence the future management of this neglected pathogen. RECENT FINDINGS: New-generation artemisinin combination therapies (ACTs) have shown potent efficacy against the erythrocytic stages of both drug-resistant P. vivax and Plasmodium falciparum. Antimalarial regimens containing slowly eliminated drugs provide a measure of protection against the first, and possibly second, relapse of tropical strains of P. vivax, but reliable radical cure is needed to prevent future relapses. Primaquine is currently the only licensed hypnozoitocidal treatment, but requires long treatment courses and its effectiveness in different endemic settings remains largely unknown. SUMMARY: In regions coendemic for P. vivax and P. falciparum, a unified treatment policy for malaria of any parasitological cause is likely to confer the greatest individual and public health benefit. Optimizing the safety and effectiveness of primaquine through the development of rapid diagnostic tests for glucose-6-phosphate dehydrogenase deficiency and improving drug adherence will be crucial endeavors in the fight against vivax malaria.